Autism spectrum disorder: The program Unstuck & On target to increase the cognitive flexibility in children with this diagnostic (Ágora de Heterodoxias, 2016)
In Venezuela works different organizations, institutions and centers where care is given to children diagnosed with Autism Spectrum Disorder (ASD). However, there are few institutions where teach the parents how to interact with infants who have ASD. This shortage creates a gap in the tutorial action of parenting, in which the parents lack of the assertive tools to reorient healthier ways of the family as a whole. Hence in this article we have set as a goal: to present the Unstuck & On target (UOT) program by Cannon Kenworthy, Alexander, Adler-Werner and Anthony (2011) to increase cognitive flexibility and executive functions of children with ASD. To achieve this objective a review of the literature was conducted, with emphasis on two converging aspects a) review of contributions of neuroscience to incorporate some findings in the everyday life of children diagnosed with ASD, b) The Unstuck & On target (UOT) that focuses on the provision of cognitive flexibility. It concludes: ASD is a complex disorder of health that can ensure the successful integration of children with the syndrome in the society and the control of symptoms when the syndrome is detected early and the psychoeducation is served parents, and the children with this complex developmental disorder.
Keywords: autism spectrum disorder; cognitive neuroscience; Unstuck & On target program; cognitive flexibility; executive function